2023
DOI: 10.3390/catal13060996
|View full text |Cite
|
Sign up to set email alerts
|

Exsolved Nanoparticles Decorated Double Perovskites as High-Performance Anodes for Direct-Ammonia Solid Oxide Fuel Cells

Abstract: Due to the high energy density, mature production technology, ease of storage and transportation, and the no carbon/sulfur nature of ammonia fuel, direct-ammonia solid oxide fuel cells (DA-SOFCs) have received rapidly increasing attention, showing distinct advantages over H2-fueled SOFCs and low-temperature fuel cells. However, DA-SOFCs with conventional Ni-based cermet anodes still suffer from several drawbacks, including serious sintering and inferior activity for ammonia decomposition, strongly limiting the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2025
2025

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(2 citation statements)
references
References 69 publications
0
2
0
Order By: Relevance
“…26 Experimental studies have confirmed that several metals can be precipitated from the perovskite lattice, including noble metals such as Pt, Pd, Rh, Ru and Ag, TMs such as Fe, Co, Ni and Cu, and their specific alloys. 27–33 This is attributed to the high reactivity of noble and TMs, making them ideal materials for the surface generation of metal NPs under reducing conditions. In particular, as nano-catalysts, B-site transition metal cations exhibit robust (electro)chemical catalytic activity and have found a wide range of applications in areas such as photo-/thermal catalysis and energy conversion.…”
Section: Introductionmentioning
confidence: 99%
“…26 Experimental studies have confirmed that several metals can be precipitated from the perovskite lattice, including noble metals such as Pt, Pd, Rh, Ru and Ag, TMs such as Fe, Co, Ni and Cu, and their specific alloys. 27–33 This is attributed to the high reactivity of noble and TMs, making them ideal materials for the surface generation of metal NPs under reducing conditions. In particular, as nano-catalysts, B-site transition metal cations exhibit robust (electro)chemical catalytic activity and have found a wide range of applications in areas such as photo-/thermal catalysis and energy conversion.…”
Section: Introductionmentioning
confidence: 99%
“…In the past decade or so, ammonia has emerged as a green energy carrier due to zero-carbon emissions upon decomposition and on-site utilization [2,3]. The most important merit of ammonia is that it can be liquified at mild conditions (at ambient temperature under about 10 atm or at −33 • C under atmospheric pressure), which makes its storage and transportation much easier than that of hydrogen [3][4][5]. Additionally, in terms of explosibility, ammonia is safer than hydrogen owing to its narrower flammability range [6].…”
Section: Introductionmentioning
confidence: 99%